Anthropological approaches to understanding consumption patterns and consumer behavior - Chkoniya, Valentina, 1977-; Madsen, Ana, 1977-; Buxrašvili, Paata, 1960- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book provides an anthropological approach to the study of consumption patterns and consumer behavior"--Provided by publisher"--